Survival of seed-coated microbial biocontrol agents during seed storage - Jürgen Köhl; Liesbeth van der Heijden; Patrick Butterbach; Typhanie Gaildry; Lia Groenenboom-de Haas; Ilse Houwers; Ezra de Lange; Giovanny Lopez; Anita van Nieuwenhoven; Maria Touceda (Biological Control, 2025)
Biological control of seedborne pathogens and soilborne seedling pathogens through antagonists applied on seeds is an alternative to chemical seed treatments. The survival of coated microorganisms during the various seed processing, storage and distribution steps is essential for the use of beneficial fungi or bacteria on seeds. A study was done to gain insight into the survival potential and variability in survival of representatives of different microbial groups during storage of coated seeds of different crops. Survival of inocula on seeds of Brassica, onion, spinach and perennial ryegrass was tested by plating and for a subset of coated seeds by viability qPCR. A close correlation was found for CFU counts per seed and the estimated number of viable conidia based on strain-specific or generic fungal viability qPCR for conidia of Cladosporium cladosporioides H39 coated on various seed lots. For Lysobacter enzymogenes 3.1 T8, viability qPCR showed survival of cells on coated seeds. However, only few colonies were produced on Tryptone soy agar. Generic fungal and bacterial qPCR and viability qPCR assays with non-coated seeds indicated that only a proportion of the seed microbiota, frequently less than 10 %, are viable. Survival of inocula coated on seeds and stored for three to six months differed between applied microbial groups, formulation of inocula and between laboratories conducting the experiments. From the obtained results it can be concluded that there is a promising potential to improve the often envisaged low survival of inocula coated on seeds. Improved strains selection, improved and adapted seed processing technologies, and developing expertise in microbial seed processing will allow the use of a broader range of fungal and bacterial groups. The application of viability qPCR will support this development as a fast and reliable tool to monitor the survival of microbial inocula coated on seeds.